THE ROLE AND SIGNIFICANCE OF HEALTH EDUCATIONAL WORK IN PEDIATRIC NURSING - Anita Štih; Majda Oštir; Maja Djokić; Maja Čamernik; Ana Jalšovec; Judita Kolenc; Sanja Ževart; Tadeja Logar Dolinšek; Almedina Alibašić; Erika Šmid (The Society for Children with Metabolic Disorders, 2023)
Health education is part of the professional activities of healthcare. Health education at the tertiary level differs from health education at the primary and secondary levels. Chronic patients - children and their parents/caregivers are a susceptible population and require even more careful treatment. A comprehensive approach is necessary, which is directed towards the entire family. The acquisition of knowledge must be systematic, pre-planned and also verified. It is appropriate to involve other professionals in the treatment, such as a: psychologist, social worker, community nurse, teachers in school, or educators in a childcare institution.